Effectiveness Of Bod Removal From Domestic Sewage In Constructed Wetland Using Pilot Scale Study - Zakaria, Iqmal Aiza (Universiti Sains Malaysia, 2022)
Domestic sewage is wastewater generated by human activity in residential, commercial, institutional, and industrial settings in which the domestic wastewater is segregated from the industrial wastewater. Domestic sewage concentrations for pollutants may vary according to the different sources of generated sewage from the SPAN Guidelines standard design parameters. Characterization of the wastewater were carried out to determine the information regarding the concentration of the pollutant present. Chemical synthetics were added to the sewage which results in similar pollutant concentration to the ideal influent which can reflect an actual performance of pollutant removal. The performance of constructed wetlands is governed by the types of constructed wetland, vegetation, and filter medium utilised in the bed. By using a pilot scale constructed wetland as a medium, the investigations of the constructed wetland system were examined for the effectiveness of BOD removal in this study. The study was carried out over a period of three weeks, with sampling done in each pond: nutrient pond, treatment pond and open pond. Grab samples of wastewater collected from different stages of treatment were tested for BOD5. The wetland was found to have a very high efficiency of removal of BOD with relatively little variability between the weeks. The three-week average BOD removal efficiency was approximately 91.8%. In terms of system comparison, subsurface flow constructed wetlands outperformed surface flow constructed wetlands in the removal of BOD. The effectiveness of elimination of BOD was high throughout the study period for subsurface wetland with the average removal efficiency of 95.17% compared to surface wetlands with 91.8%. In hybrid systems such as in this pilot scale study, the advantages of the SSF and SF systems can be combined to complement processes in each system to produce an effluent low in BOD.